P177 High prevalence of unrecognised asthma in children with sickle cell disease. (15th November 2016) - Akthar, M; Ruiz, G; Chakravorty, S; Bossley, C; Rees, D; Gupta, A
Abstract : Background: Sickle Cell Disease (SCD) affects about 1 in 1, 900 children born in the UK. Respiratory morbidity affects children as well as adults with SCD and the burden may have been underestimated in the past. The published literature suggests that asthma, airway hyper-reactivity and sleep disordered breathing (SDB) are common in children with SCD. Furthermore asthma and SDB have been reported to be associated with acute chest syndrome (ACS) and vaso-occlusive crises (VOC). Children with SCD are increasingly referred to our respiratory clinic in a tertiary paediatric centre in the UK. We did an analysis of a sample of these children to gain some preliminary insights into the problem. Method: A retrospective observational study was carried out using data from children with SCD who had been referred to our tertiary paediatric respiratory clinic between 1 st September 2009 and 31 st August 2014. Data was collected from electronic patient records and electronic investigation results. Results: 54 patient records were evaluated. The mean age of the children was 11 years and 54% were male. The most common reason for referral was low oxygen saturation on pulse oximetry (23/54). Surprisingly, asthma and wheeze were uncommon reasons for referrals comprising only 7/54 (Figure 1 ). However, of all the patients 48% were discovered to have asthma and 52% had SDB. In those patients who underwent lung function testing an abnormal result was reported in 60% (25/42). In addition 71% of children who had a sleep study had an abnormal result (35/49). No association between ACS or VOC events in those patients with asthma or SDB was noted but this could have been due to the small numbers. Conclusion: In this sample of children with SCD referred mainly because of low oxygen saturation, the high proportion with an abnormal sleep study and SDB might have been expected. However, the relative paucity of reported wheeze and exercise intolerance despite large numbers with abnormal lung physiology suggested that conditions such as asthma may be unrecognised in these patients.